THE IMPACT OF MOTIVATION ON EFL LEARNERS’ WRITING PERFORMANCES. - Korichi , Abderrazak; Bahloul, Amel (Journal of Social Sciences and Humanities, 2021)
Motivation has often been considered as the most important factors that affects English learning performance. Researchers mentioned that despite other factors influencing language learning and acquisition, the one of motivation is the most important. It is generally believed that motivation enhances EFL students ‘writing competences. It is a multifaceted concept that has been the subject of several researches in different areas and particularly in English. It has a major role in achieving many goals in students ‘academic life particularly in writing process. Therefore, motivation is considered as the pushing wheel of the vehicle used by the learner to achieve their educational aims. This paper investigates the role of motivation on EFL learners’ writing performances among the undergraduate students at the department of foreign languages at the University center of Barika (Batna). It shows whether these students are instrumentally or integratively motivated to study and then to write in English language, starting by dealing with a review of the literature related to the concept of motivation and writing skill, followed by collecting data through a questionnaire submitted to these participants, then analyzing and interpreting data. Furthermore, the findings revealed that our sample is moderately instrumentally and integratively motivated to learn and then to write in English language. Finally, this study concluded that these students have a good record in writing skill because of their motivation, which enhances their fluency and performance in the use of English language in a perfect way.